Science on ice: Discovering the secrets of Antarctica - Curtis, Neil (New Zealand Science Review, 2012)
​Veronika Meduna is a science journalist who has made a number of professional visits to Antarctica, mainly to the McMurdo Sounds region where most of New Zealand’s research activity occurs. This work is a composite of her impressions, and of interviews with scientists both in the field and back in the laboratory. These are extended by accounts of related studies by scientists from other countries, usually with some New Zealand connection. It includes physical, geological and biological aspects and is laced with relevant historical anecdotes. The study provides a useful introduction to New Zealand Antarctica, but falls between two stools, probably including more scientific detail than the casual reader would like, but less than an interested scientist might appreciate. The book is very well produced with many brilliant photographs and would grace any intelligent coffee table and be an asset in any school library.